(untitled) (Global Journal of Human-Social Science, 2020)
The phenomenon of indecent workplaces poses serious existential threats to profits plants and people including the attainment of sustainable development goal SDG in Sub-Saharan Africa This chapter discusses the imperative of transition to decent work and economic growth in Sub-Saharan Africa a move that is expected to lead to the attainment of SDG 8 Using a mixed research method with preference for secondary data the paper provides richer findings on the subject of inquiry It was found that the per capita GDPs of Sub-Saharan Africa a period of 10 years 2000-2019 are very low when compared with the minimum per capita GDP of 3996 for the Upper-Middle Income countries Also the continent manifested a low tendency towards decent work because of worsening unemployment rates and higher vulnerable employment in the labour force With regards to practical and managerial implications the study validates the United Nations targets on economic growth and decent work which explicates that to sustain per capita economic growth the least developed countries must have at least 7 percent gross domestic product growth per annum including providing decent work for all women and men